An Analysis of Insertional Code – Mixing Found in Merry Youtube Channel: The Cinta Laura Episode - Kadek Ayu Swandewi; I Wayan Juniartha (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study examines the phenomenon of insertional code-mixing in the YouTube podcast conversation between Merry Riana and Cinta Laura, focusing on the forms, functions, and motivations behind its use. Employing a descriptive qualitative method, the research analyzes verbatim transcriptions of the podcast episode “Cantik, Pintar & Sukses, Cinta Laura Merasa Tidak Bahagia Dalam Hidupnya?” (2022), which has a duration of 65 minutes. A total of 15 instances of insertional code-mixing were identified and analyzed using Muysken’s (2000) theoretical framework. The study specifically investigates the insertion of English words and phrases into Indonesian syntactic structures. The findings reveal that Cinta Laura strategically employs code-mixing not merely as a linguistic habit but as a communicative tool. Insertions are used to emphasize ideas, express emotions, and construct her identity as a modern, reflective bilingual speaker. Examples show that English insertions enhance clarity, add philosophical depth, carry prestigious value, and foster emotional intimacy with the audience. In conclusion, Cinta Laura’s use of intra-sentential code-mixing is a dynamic linguistic practice that enriches her communication and shapes her public persona. Her selective use of English terms within Indonesian sentences enables more precise and impactful message delivery. This study underscores the broader significance of code-mixing as a sophisticated strategy for bilingual speakers in digital environments. It highlights how bilingual individuals leverage their linguistic repertoire to navigate complex topics, express vulnerability, and build stronger connections with online audiences.